Inovasi teknologi budidaya bawang dayak (Eleutherine palmifolia Merr) untuk meningkatkan produktivitas dan analisis kelayakan ekonomi - Titin Apung Atikah; Tatik Wardiyati; Ellis Nihayati; Saputera Saputera; Doppy Roy Nendissa (Fakultas Pertanian Universitas Yudharta Pasuruan, 2021)
Dayak onions (Eleutherine palmifolia Merr) are a potential commodity that has many health benefits, so it has a high economic value. However, this Dayak onion plant has not received much attention in cultiva¬tion technology, especially fertilization. So far, this onion has grown relying on nature, while the land has diminished its fertility. This study tested a combination of chicken manure and NPK fertilizer to obtain the optimal composition to increase the productivity of Dayak onions. This study used a factorial randomized block design with 3 replications. The first factor consists of the treatment of chicken manure(O1 = control, O2 = 10 ton.ha-1 and O3 = 20 ton.ha-1). The second factor consists of NPK fertilizer(K1 = control, K2 = 100 kg.ha-1 Urea + 150 kg.ha-1 SP 36 + 200 kg.ha-1 KCl, K3 = 200 kg.ha-1Urea + 150 kg.ha-1 SP 36 + 200 kg.ha-1 KCl, and K4 = 300 kg.ha-1 Urea + 150 kg.ha-1 SP 36 + 200 kg.ha-1 KCl). The results showed that there was an interaction effect between the composition of chicken manure and NPK on the number of leaves, fresh weight of tubers, and dry weight of tubers per clump but did not affect the growth of plant height. The yield of Dayak bulbs of 62.60 g / clump was obtained in the composition of chicken manure of 20 tonnes.ha-1 with an NPK of 200 kg.ha-1 Urea + 150 kg.ha-1SP 36 + 200 kg.ha-1 KCl. From an economic perspective, the composition is very efficient and feasible, which is indicated by R / C> 1, namely 5.75, which means that with a certain unit cost, it can get 5.75 times the revenue.